A DISCRETE MATHEMATICAL MODELING FOR DRINKING ALCOHOL MODEL RESULTING IN ROAD ACCIDENTS AND VIOLENCE: AN OPTIMAL CONTROL APPROACH. (2021) - YOUSSOUFI, LAHCEN EL; KHAJJI, BOUCHAIB; BALATIF, OMAR; RACHIK, MOSTAFA
No abstract available